Evaluation of cardiac regeneration through electrocardiograms in Danio rerio in state of hypobaric hypoxia (2025)
Cardiovascular diseases remain a leading cause of mortality globally. Heart failure often results in irreversible damage and the formation of non-contractile fibrotic scars that are not capable of proper electrical transmission as they are not an adequate substitute for cardiomyocytes. The scars are made of a non-contractile collagenous tissue that thins and compacts over time, increasing stress to the heart walls causing problems such as arrhythmias. Current research focuses on regenerative approaches to restore the lost cardiac tissue, using model organisms such as zebrafish (Danio rerio) due to their heart regeneration capacity, and similarities to humans in cell composition and electric activity. This study investigates the effects of hypobaric hypoxia on the regeneration processes as the hypoxia-inducible factors (HIF) have been seen to change cell metabolism, management of oxidative stress, and angiogenesis likely affecting heart electric activity. This was functionally visualized following the ventricular regeneration process after cryoinjury using electrocardiogram (ECG) analysis. Thus, we assess the cardiac electrical activity throughout the regeneration process of the zebrafish comparing a state of normoxia and a state of hypobaric hypoxia. All ECG data were processed through a principal component analysis, which revealed possible differences in cardiac recovery patterns between hypoxic and normoxic groups. Hypoxia-exposed zebrafish demonstrated potentially faster heart rate recovery, shorter RR intervals, likely influenced by chronic hypoxia adaptations such as enhanced HIF-1α expression and increased sympathetic nerve activity. These findings suggest that hypoxia could make the regeneration process more efficient, and prepare the heart for events of heart failure, which correlates with studies of humans permanently residing in high-altitude regions.